A case study of a blind speaker of English as L2 - Geld, Renata (Array, 2009)
This paper upholds the cognitive linguistic view that language and knowledge are experiential phenomena, and that they are tightly related to the way we conceptualize reality (cf. Lakoff, 1987 ; Langacker, 1987, Talmy, 1988a ; 1988b ; 2000). In order to support this idea we present a case study of a blind speaker of English as L2, which offers an insight into differences in conceptualization due to different perceptive abilities, in this case the lack of vision. Furthermore, we attempt to show that blindness itself does not in any way determine the level of language proficiency, but that it does affect the way linguistic meaning is constructed. The paper explores mental imagery, that is, a dynamic and subjective process of constructing linguistic meaning (Langacker, 1987), of a legally blind person in the process of learning English as a second language. The main hypothesis was based on the findings from two previous studies (Geld and Starčević, 2006 ; Geld and Stanojević, in press) whose results suggest that the conceptual content in the language of the blind indicates a specific realization of two cognitive processes as aspects of meaning construal: firstly, there is a shift in scalar adjustment from schematicity to specificity, and secondly, the vantage point tends to indicate a different position of the conceptualizer. Thus, we hypothesized that a close examination of the subject’ s second language would reveal aspects of meaning construal identified in the first language and found in the group of blind subjects examined in the above mentioned studies. Furthermore, it was our intention to investigate potentially idiosyncratic phenomena in second language processing in a blind person with a specific impairment. Finally, we aimed to demonstrate how the particular efficiency of using residual vision and the resulting experience of reality is reflected in a second language.